Historical Traces of Sriwijaya's Influence in the Portibi Region: A Historical Study of the Bahal Temple Complex in North Padang Lawas - Aftitah Harahap; Hotmatua Paralihan (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
This study examines the historical traces of Sriwijaya's influence in the Portibi region through a historical investigation of the Bahal Temple Complex in North Padang Lawas, a site whose role within Sriwijaya's regional network remains insufficiently explored in Indonesian historiography. The study reconstructs the historical background of the temple complex, identifies archaeological and historical evidence reflecting Sriwijaya's influence, and analyzes its significance within the cultural landscape of the Pannai Kingdom. The research employs the historical method through the stages of heuristics, source criticism, interpretation, and historiography, supported by field observations, interviews with relevant stakeholders, and documentary analysis of scholarly publications, archaeological reports, and official records. The findings demonstrate that the Bahal Temple Complex, an eleventh-century Vajrayana Buddhist monument, preserves historical traces of Sriwijaya's influence through its architectural characteristics, red-brick construction, spatial organization, Buddhist iconography, and strategic location along an ancient riverine transportation network. These findings indicate that the Portibi region formed part of a wider political, religious, and commercial sphere associated with the Pannai Kingdom under the influence of Sriwijaya. This study contributes to Indonesian historiography by integrating historical, archaeological, and geographical evidence to provide a more comprehensive interpretation of Sriwijaya's regional influence in North Sumatra while reinforcing the historical importance of the Bahal Temple Complex as one of the most significant archaeological legacies of the Sriwijaya period.